Gender and access to cowpea innovations in West Africa: a review of some critical issues - Adetonah, S.; Nouhoheflin, S.T.; Aitchedji, C. (International Institute of Tropical Agriculture, 2012)
Cowpea provides food and incomes to farm households including women farmers who make and sell snack foods from this nutritious legume in West Africa. Gender roles are important in cowpea value chains. The main constraints reported by women are poor access to cowpea innovations, opportunities, and related capacity building. The overall objective of this paper is to review key constraints and opportunities for an effective inclusion of women in cowpea value chains through access to innovations using a genderdisaggregated database and other information. The study uses a sample of 549 producers including women across Mali, Niger, and Nigeria in West Africa. Cowpea baseline survey results showed that the proportion of men as head of household is slightly higher than women. In northern Nigeria, men would grow cowpea for incomes and then food while women would grow cowpea for home consumption and feed for small ruminants. Feed and grains are provided by dual-purpose cowpea varieties whose adoption is constrained by insect attacks both in the field and in storage, drought, nematodes, and the lack of effective seed supply systems. In Nigeria there were no significance differences between men and women for access to inputs such as fertilizers, pesticides, and insecticides, but access to seeds and agricultural equipment for women was limited because men have to finish plowing their land before helping women . In Mali, women use storage technologies, particularly solar drying because they often do not have access to storage insecticides. In all the countries most of the women farmers do not have control over their productive assets and on-farm incomes. Women farmers reported the need for credit to purchase seeds in all the countries and contribute mostly to farming activities like threshing, variety choice storage, and marketing in Mali and Niger.